Wie se grond koop Boas (Rut 4:9)? - S. L. Stassen (Acta Theologica)
In Ruth 4:3 it is stated that Naomi “is selling  the piece of land” that belonged to Elimelech, her late husband. In Ruth 4:5 the redeemer is asked to buy the piece of land from the hand of Naomi , and in verse 9 Boaz declares that he will buy the piece of land from the hand of Naomi . According to the language in the Hebrew text, it seems that Naomi was doing business as the rightful owner of the piece of land. According to the laws and customs in the times of the judges,however, a widow was not allowed to inherit land from her husband, and a woman was not allowed to own, buy or sell land. In this article the following possibilitiesare investigated: Either the writer of the Ruth narrative was so far removed from the time of Ruth that he did not know the customs and laws in the time of the judges, or different laws could apply to different periods in the time of the judges or to different communities in the time of the judges, or the verbs “to sell” in 4:3 and “to buy” in 4:5 and verse 9 should be understood in a different manner than convention permits us to do.